Depletion of Nsd2-mediated histone H3K36 methylation impairs adipose tissue development and function - Lenan Zhuang (Nature Portfolio, 2018)
The epigenetic mechanisms regulating adipose tissue development are poorly understood. Here the authors show that reduction of H3K36 methylation in preadipocytes, both by H3.3K36M expression and depletion of H3K36 methyltransferase Nsd2, impairs adipogenesis by increasing H3K27me3.